Pengaruh Pemberian Fitobiotik dari Ekstrak Kulit Jengkol dan Probiotik Bacillus cereus terhadap Profil Imun Darah Itik Magelang Jantan - Mikael Sihite; Pradipta Bayu Aji Pramono; Tiara Afifah (Fakultas Peternakan Universitas Halu Oleo, 2023)
Improving the body immune of male magelang ducks can be done through the administration of a combination of phytobiotics and probiotics as a substitute for antibiotics. The purpose of this study was to determine the effect of the combination of phytobiotics from jengkol peel extract with the probiotic Bacillus cereus on the immune profile of male magelang ducks. This research was carried out for 8 weeks of rearing which was carried out in the poultry house of the Faculty of Agriculture, Tidar University and analysis of blood profile was carried out at the Laboratory of the Prof. Soeparwi Veterinary Hospital, Faculty of Veterinary Medicine, Gadjah Mada University. The research used 100 male Magelang ducks DOD grouped into 5 treatments, namely (P0) control water without the addition of probiotics and extracts; (P1) water with the addition of 0.5% probiotics and 0.2% jengkol peel extract; (P2) water with the addition of 1% probiotics and 0.4% jengkol peel extract; (P3) water with the addition of 1.5% probiotics and 0.6% jengkol peel extract; (P4) water with the addition of 2% probiotics and 0.8% jengkol peel extract. The data was analyzed using SPSS Version 23 software using a completely randomized design (CRD) with a unidirectional pattern, then continued with the Duncan Multiple Range Test (DMRT). The results showed that the combination of phytobiotics from jengkol peel extract with Bacillus cereus no significant effect (P>0.05) on the hemoglobin, eritrocyte count and leukocyte level of male Magelang ducks. The conclusion of this study was the combination of phytobiotics from jengkol peel extract with probiotic Bacillus cereus did not affect the hemoglobin, eritrocytes count and leukocytes level in male Magelang ducks.